Meaning of Tutorial Practices in the Counseling Students in Master of Education Thesis - Santa Cruz Terán, Flor Fanny (2018)
The purpose of this study is to understand the meaning that Master of Education students attribute to tutorial practices during thesis counseling sessions. The work was developed according to a qualitative approach with phenomenological design, based on the participant observation and the indepth interview. The data were analyzed through a set of thematic codes, through a process of coding obtained from the units of significance of a content and discourse analysis. The findings allows to understand that friendly communication, trust, motivation and a good emotional climate are present in the interactions between the advisor and the person being counseled, which shows the effectiveness of the technological didactic resource in the counseling.